Inovasi Media Pembelajaran Seni Tari Berbasis Web Articulate Storyline 3 - Wangi, Baiq Addina Azza Awlia; Padlurrahman, Padlurrahman; Murcahyanto, Hary (JOEAI (Journal of Education and Instruction), 2026)
This study aims to develop and evaluate interactive web-based learning media in Articulate Storyline 3 to increase student motivation for learning in high school dance lessons. The research method used was research and development (R&D), and experts in materials, media, and language validated the developed product. The results showed that this media was efficient and effective, with an average score of 89% across ease of use, usefulness, product appeal, and media use. Field testing demonstrated that this media can increase student motivation to learn, with post-test scores in the experimental group higher than those in the control group. This media offers an innovative solution to overcome the limitations of conventional media in dance lessons, while providing an interactive and enjoyable learning experience. This research contributes to the development of web-based learning media that can be effectively implemented in schools. In conclusion, interactive web-based learning media created with Articulate Storyline 3 have proven effective in increasing student motivation during dance lessons.   Keywords: Articulate Storyline3, Learning Media, Learning Motivation, Dance